Diagnostic approach to encephalitis and meningoencephalitis in adult returning travellers. (April 2019) - Kenfak, A.; Eperon, G.; Schibler, M.; Lamoth, F.; Vargas, M.I.; Stahl, J.P.
Abstract: Background: Encephalitis and meningoencephalitis are severe, sometime life-threatening infections of the central nervous system. Travellers may be exposed to a variety of neurotropic pathogens. Aims: We propose to review known infectious causes of encephalitis in adults acquired outside Europe, and how to identify them. Sources: We used Pubmed and Embase, to search the most relevant publications over the last years. Content: Microbiologic tests and radiological tools to best identify the causative pathogen in travellers presenting with encephalitis and ME are presented in this narrative review, as well as a diagnostic approach tailored to the visited area and types of exposures. Implications: This review highlights the diagnostic difficulties inherent to exotic causes of central nervous system infections, and attempts to guide clinicians with respect to which microbiological tests to consider, in addition to brain MRI, when approaching a returning traveller presenting with encephalitis.